Food security of Kazakhstan: state and opportunities - A. A. Satybaldin; G. K. Temirova; T. A. Zhunisbekova (Экономика: стратегия и практика, 2020)
This article discusses the importance and role of food security in the current economic situation. Food security is considered an important condition of existence and independence of the state. The current situation is characterized by a complex social complex of modern demands, aimed at solving political, environmental and other problems at the international level, as well as at the level of each country in the world community. Problems of food security also require in-depth research in the field of agriculture. Coordinated work in the field of biotechnologies aimed at improving agricultural crops, innovative strategies in the field of processing and production in agriculture, stimulating the introduction of new technologies in the food industry and attracting investment in research projects in this area can serve as a guarantee of food security of the Republic of Kazakhstan.The study presents the results of the consumption of certain types of agricultural products in the population. National food consumption standards were compared with physiological consumption norms, and a regional aspect of population consumption was studied from the point of view of minimum and maximum consumption. In addition, the following system of measures is proposed to eliminate internal and external threats to national food security.